Sobrevida de pacientes con cáncer de mama Her2 positivo tratadas en el Hospital de Solca Loja - Macas Cabrera, Brayan Edison (2019)
Breast cancer HER2 positive (BRCA HER2 +) represents 20 to 30% of breast cancers, until before biological therapies was the most aggressive, with a 5-year survival of 74%. This is why arises the need for the current research whose main objective was to determine the 5-year survival in patients with BRCA HER2 + treated at the Hospital of SOLCA Loja from 2007 to 2011, this is a non-experimental cross-sectional type, retrospective descriptive study, we worked with 40 patients, the data was analyzed in SPSS 23.0 and Excel, descriptive frequency analysis, Kaplan-Meier method for survival, and Log-Rank were used. Results: The BRCA HER2 + represented the 13% (40 cases) of all breast cancers, the 22.5% (9 cases) in women of 40-44 years, the 43% (17 cases) was diagnosed in stage II. The 5-year survival was of a 96% for stages I and II, 73% for stage III, and 28% for stage IV, Log-Rank 0,000002. The 5-year survival for patients who did not receive trastuzumab was 81%, for those who received less than 8 cycles it was 80%, from 9 to 14 cycles 85%, and 100% for more than 15 cycles. Conclusions The incidence of BRCA HER2 + is lower than in other latitudes, the survival varies slightly to that described by other researchers. Keywords. Trastuzumab, survival, HER2, stage.